Human-Technology Interaction: An Automated Border Control System in Indonesia - Yanwar Iswahyudi Mansur; Semiarto Aji Purwanto (Eduvest - Journal of Universal Studies, 2024)
As automated border control systems become increasingly prevalent worldwide, their implementation in Indonesia presents challenges and opportunities at the intersection of technology and society. This literature review examines the social and technological dimensions of interactions with automated border control systems in Indonesia, focusing on the evolving dynamics between citizens, technology, and government. The review highlights how automated systems, while enhancing efficiency, also transform traditional notions of border crossing inspections. This study explores four key aspects, human-technology interaction with their positive and negative impact, biometrics technology on immigration checkpoints, social interaction impact on automated border control system, and the shift in government-society relationships in the context of technology-based services. By synthesizing existing literature and case studies, this review aims to provide insights into the socio-technical landscape of border control automation in Indonesia. Currently, there are not many studies that focus on discussing the impact of the loss of social interaction in the implementation of information technology in public services, especially in automated border control. It is essential to carefully consider the disadvantages and explore ways to address them before fully embracing the automated immigration clearance system. These findings might have significant implications for policymakers, technology developers, and social scientists, offering an understanding of how automated systems reshape social interactions and institutional relationships in the critical domain of border security and management.